Collagen‐like Cell‐Penetrating Peptides1. Issue 21 (16th April 2013) - Yamazaki, Chisato M.; Nakase, Ikuhiko; Endo, Hiroyuki; Kishimoto, Saya; Mashiyama, Yoshihiro; Masuda, Ryo; Futaki, Shiroh; Koide, Takaki
<x xml:space="preserve">Abstract</x> Arginine‐rich heterotrimeric collagen‐like peptides were prepared, and their cellular uptake efficiency was evaluated. The spatial arrangement of the Arg residues (blue in picture) on the triple‐helix surface significantly affected the efficacy of the cellular uptake. The collagen‐like triple‐helical conformation provides these cell‐penetrating peptides with a high resistance to proteases. O=L‐4‐hydroxyproline.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>